Breakthrough filamentous fungal infections in pediatric hematopoetic stem cell transplant and oncology patients receiving caspofungin - Morris, Shaun K (Pulsus Group Inc, 2012)
BACKGROUND: Caspofungin is an echinocandin class antifungal medication that is commonly used empirically in immunocompromised patients at high risk for invasive fungal disease. OBJECTIVE: To describe the clinical characteristics of breakthrough fungal infections in pediatric hematopoetic stem cell transplant recipients, and oncology and hematology patients receiving caspofungin. METHODS: A five-year retrospective review, from 2004 through 2008, of all cases of proven invasive filamentous fungal infection of children admitted to The Hospital for Sick Children (Toronto, Ontario) was conducted. A breakthrough infection was defined as new onset of symptoms that were later proven to be due to an invasive mold infection on day 3 or later after initiation of caspofungin therapy. RESULTS: Six confirmed positive cultures (Aspergillus fumigatus [two cases], Aspergillus niger, Fusarium oxysporum, Alternaria infectoria and Rhizomucor pusillus) met the criteria for breakthrough filamentous mold infection while on caspofungin therapy. Underlying immunocompromising conditions included acute lymphoblastic leukemia (two cases), acute myeloid leukemia (two cases), Burkitt’s lymphoma and aplastic anemia. Four of the patients underwent a hematopoetic stem cell transplant. All patients received a lipid amphotericin B product as part of their treatment for breakthrough infection. Five patients also received voriconazole and one received posaconazole. Four of the six patients died and two responded with a clinical and microbiological cure. DISCUSSION: There are few descriptions of breakthrough fungal infections in pediatric patients receiving caspofungin. The six cases presented here, all microbiologically proven, are likely only a fraction of the total number of possible breakthrough invasive fungal infections that occured over the study period. CONCLUSION: Clinicians must remain aware that breakthrough fungal infections by species not covered by particular antifungals, including caspofungin, do occur and may have poor outcomes.